Multiple acyl-CoA dehydrogenation deficiency: defects of electron transfer flavoproteins - Olsen, Rikke (Henry Stewart Talks, 2007)
Multiple acyl-CoA dehydrogenation deficiency (MADD), Glutaric aciduria type II (GAII), Electron transfer flavoprotein (ETF), ETF: ubiquinone oxidoreductase (ETF:QO), Biogenesis and function of electron transfer flavoproteins, Genotype-phenotype relations, Molecular genetic pathogenesis, Treatment and diagnosis
Archived at 2020/08/13